Random Lasing in wide-gap semiconductor thin films under deep UV pulsed laser pumping. (2017) - Cachoncinlle, C.; Millon, E.; Petit, A.; Nistor, M.
Abstract: We present a comparative study of spectral features of random lasing in GaN and ZnO semiconductor films. Numerical calculations of the complex susceptibility are carried out for different carrier concentrations. The absorption coefficients, refractive indices, and theoretical Mott densities are deduced from these calculations in the vicinity of the optical bandgap. As expected in such materials, above the Mott density, calculations highlight the specific spectral domain for each semiconductor where an optical gain may take place. Semiconductor films are optically pumped using a pulsed NdYAG laser at 266 nm, and photoluminescence spectra of the near band edge are investigated at low and high spectral resolution (down to 50 pm). Dependence of the random laser emission upon the thickness of ZnO films is studied. It is demonstrated that random lasing is sustained by waveguiding propagation in the plane of films.